"Leia, considere, marque": análise e descrição sistêmico funcional da avaliação escolar voltada ao ensino médio no português brasileiro - Azevedo, Laura Scaramussa (2024)
This work is affiliated with Systemic-Functional Linguistics (Halliday; McIntosh; Strevens, 1964; Eggins, 2004; Halliday; Matthiessen, 2014), a branch of Functional Linguistics that has a strong interest in the investigation of texts within the environment of basic education (Halliday, 1998; Christie, 2004; Martin; Rose, 2005; Christie; Martin, 2007; Rose, 2019). Based on these studies, the research aims to analyze the SCHOOL EXAM as a genre through Genre Pedagogy, also a prominent area of study within SFL (Martin; Rose, 2007; Rose, 2012). The work seeks the discussion of texture in SCHOOL EXAMS, considering the concept of text within the theory, as well as describing it in terms of its schematic structure, detailing stages and phases, and proposing a way to visualize the description of genres according to the theory. Methodologically, the study uses methods common to research conducted within the SFL framework, such as lexicogrammatical analysis performed through spreadsheets, and also proposes improvements to the method. The results show a stable generic structure concerning SCHOOL EXAMS; moreover, despite the genre showing characteristics that do not follow prototypical features concerning the constitution of the texture, elements of cohesion and coherence indicate the possibility of identifying it within the genre. The lexicogrammatical investigation allowed for the observation of patterns within the systems of this stratum, making it possible to satisfactorily describe the genre in the aspects analyzed.